Paranasal sinus computed tomography findings in patients treated for lepromatous leprosy - Kiris, A.; Karlidag, T.; Kocakoc, E.; Bozgeyik, Z.; Sarsilmaz, M. (Cambridge Univ Press, 2007)
Aim: Nasal and paranasal sinus involvement is common in lepromatous leprosy and is of considerable epidemiological significance. The aim of this study was to investigate paranasal sinus abnormalities in treated lepromatous leprosy cases and to evaluate the findings in comparison with those of previous studies. Materials and methods: Thirty-eight patients who had been treated for lepromatous leprosy were included. All patients had been treated with dapsone and rifampicine for six months, and followed with dapsone, rifampicine and clofamizine for a minimum of two years. All patients received a clinical examination, a coronal computed tomography (CT) examination of the paranasal sinuses and ethmoidal sinus endoscopy, in order to investigate the involvement of the paranasal sinuses in the leprosy. Ethmoidal sinus biopsies were taken in 18 of the 21 cases of ethmoidal sinus involvement noted on CT scan. Results: Twenty-three patients had sino-nasal symptoms. Endoscopic examination showed different pathologies in 21 of these patients. Abnormalities in the paranasal CT images were observed in 27 patients. The ethmoidal, maxillary, frontal and sphenoid sinuses were affected in 21, 18, three and two patients, respectively. Various degrees of nasal septum perforation were noted in 18 cases. In six of the 18 patients biopsied, the biopsy specimen showed involvement by lepromatous leprosy. Conclusion: These findings suggest that although these lepromatous leprosy patients had been treated, persistent infection was still commonly encountered. Paranasal sinus CT examination is a useful method for the evaluation of patient response to treatment and follow up; however, a CT scan alone cannot determine whether the leprosy is active.
Keywords: leprosy; lepromatous; Paranasal sinuses; endoscopy; computed tomography